ความพึงพอใจของประชาชนที่มีต่อการบริหารงานก่อสร้างและสาธารณูปโภคของ องค์การบริหารส่วนตำบลสระนกแก้ว จังหวัดร้อยเอ็ด - โพดาพล, พิเชษฐ์ (วารสารศรีล้านช้างปริทรรศน์; Vol 1 No 1 (2015): วารสารศรีล้านช้างปริทรรศน์ ปีที่ 1 ฉบับที่ 1 (มกราคม - มิถุนายน 2558), 2015)
บทความเรื่องความพึงพอใจของประชาชนที่มีต่อการบริหารงานก่อสร้างและสาธารณูปโภคขององค์การบริหารส่วนตำบลสระนกแก้ว จังหวัดร้อยเอ็ด มีวัตถุประสงค์เพื่อศึกษาระดับความพึงพอใจของประชาชนที่มีต่อการบริหารงานก่อสร้างและสาธารณูปโภคขององค์การบริหารส่วนตำบลสระนกแก้ว จังหวัดร้อยเอ็ด โดยรวบรวมข้อมูลจากกลุ่มตัวอย่าง ประชาชนที่มีสิทธิ์เลือกตั้งในเขตพื้นที่การบริหารงานก่อสร้างและสาธารณูปโภคของเทศบาลตำบลสระนกแก้ว จังหวัดร้อยเอ็ด เพื่อนำผลการศึกษามาบันทึกข้อมูล วิเคราะห์ ประเมินผล สรุปผลความพึงพอใจของประชาชน ผู้วิจัยจึงใช้ตารางของเครจซี่และมอร์แกน เพื่อกำหนดขนาดกลุ่มตัวอย่างจากประชาชนทั้งหมด จำนวน 3,347 คน ได้จำนวนกลุ่มตัวอย่าง 346 คน เครื่องมือที่ใช้ในการรวบรวมครั้งนี้ เป็นแบบสอบถามแบบปลายปิดและปลายเปิด การวิเคราะห์ข้อมูลการสำรวจในครั้งนี้ใช้เครื่องคอมพิวเตอร์ประมวลผลด้วยโปรแกรมสำเร็จรูป SPSS และเสนอวิธีการบริหารงานก่อสร้างและสาธารณูปโภค      The objectives of this research were to study the satisfaction levels of people with construction and infrastructure management of Sanokkaew Subdistrict Administrative Organization. The population of the research was a total of 3,347 people in the service area of Sanokkaew subdistrict, Phon Thong district, Roi-et province, and 346 samples were selected by Krejcie and Morgan’s sampling method. The instruments of the research were comprised of closed-ended and open-ended questionnaires, and the data were collected, statistically analyzed, and summarized. The Statistical Package for the Social Sciences (SPSS) was used to process the collected data, and the ways on administration of construction and public services were recommended.      The results of the research were found that satisfaction of people with this SAO’s construction and infrastructure was covered in four areas: infrastructure, civil construction or engineering personnel, transparency and accountability, and post-auditing (after completion), including various recommendations. This study could be used to make a plan of construction and infrastructure development in the future to increase efficiency and greater people’s satisfaction.